(untitled) (Journal of the College of Basic Education, 2023)
Since my doctoral studies, I have been thinking about the topic “The Impact of the Noble Prophet’s Hadith on Arabic Literature”, so I have been searching in libraries over and over between books, hoping to find a separate book with this study dealing with the impact of the Noble Prophet’s Hadith or quoting from it in the poetry of any of the poets in a detailed or analytical study, but I I found that the pens of researchers and writers have turned towards the Holy Qur’an only, so the critics and rhetoricians, past and present, have occupied themselves, and none of them has taken up the study of quoting from the honorable hadith of the Prophet in a specialized book that shows the masterpieces of his creativity (may God bless him and his family and grant him peace) despite the richness of this topic for those who wanted Going into it, despite the many pens that were written in the Prophet’s biography, as they are many and countless. For example, I did not find anyone who had been exposed to the study of the Prophet’s rhetoric and the Prophet’s statement,